2007
DOI: 10.2176/nmc.47.389
|View full text |Cite
|
Sign up to set email alerts
|

Nicardipine Prolonged-Release Implants for Preventing Cerebral Vasospasm After Subarachnoid Hemorrhage: Effect and Outcome in the First 100 Patients

Abstract: Vasospasm following subarachnoid hemorrhage (SAH) remains difficult to prevent despite extensive investigative efforts. Nicardipine prolonged-release implants (NPRIs) have been used to prevent vasospasm in patients with SAH since October 1999. The present study analyzed the efficacy and safety of NPRIs in 100 patients with SAH and thick subarachnoid clot (mainly Fisher group 3) treated with NPRIs (diameter 2 mm, length 10 mm, containing 4 mg of nicardipine) during surgery after clipping of the aneurysm. The nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…110 Approximately 236 addi tional patients have been treated in openlabel studies in Japan. 111 Targeting microthromboembolism Metaanalysis of seven randomized clinical trials of antiplatelet drugs in a total of 1,385 patients found trends towards reduction in poor outcome (RR 0.79, 95% CI 0.62-1.01) but also towards increased intra cranial haemor rhage (RR 1.36, 95% CI 0.59-3.12). 112 Further trials are needed to determine whether these drugs are efficacious in this indication.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…110 Approximately 236 addi tional patients have been treated in openlabel studies in Japan. 111 Targeting microthromboembolism Metaanalysis of seven randomized clinical trials of antiplatelet drugs in a total of 1,385 patients found trends towards reduction in poor outcome (RR 0.79, 95% CI 0.62-1.01) but also towards increased intra cranial haemor rhage (RR 1.36, 95% CI 0.59-3.12). 112 Further trials are needed to determine whether these drugs are efficacious in this indication.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Of these, nicardipine is a second-generation dihydropyridine-type calcium channel blocker that has vasodilator properties with a unique cerebrovascular profile. It is administered routinely via continuous intravenous [13] or IA infusion [14,15], or as prolonged-release implants [16,17,18]. However, as conceded in the current guidelines, the primary limitation of IA vasodilator therapy is its short duration of benefit [19].…”
Section: Introductionmentioning
confidence: 99%
“…Although this was neither a controlled, nor a blinded, investigation its findings were complemented by a summary of the first 100 patients treated with NPRIs, 8 where NPRI placement completely prevented vasospasm in vessels adjacent to the pellet, but not in more remote regions. Findings of a multicentre cooperative study on NPRIs in Tokyo was then able to confirm these findings yet again in 136 patients, where the rates of angiographic vasospasm (24.6 %), cerebral infarction (12.4 %) and DIND (8.2 %) were found to be decreased significantly.…”
Section: Summary Of Previous Investigationsmentioning
confidence: 99%